2014
DOI: 10.1111/ijd.12160
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tissue FoxP3+, CD4+ and CD8+ T‐cells in active and stable nonsegmental vitiligo

Abstract: The reduction in the number of FoxP3+ cells in the marginal skin suggests that this is the site where regulatory activity is needed to suppress the activity of helper and cytotoxic T-cells that are actively contributing to depigmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 21 publications
3
40
3
3
Order By: Relevance
“…A decrease in CD4 + /CD8 + ratio and Tregs, and reduced FoxP3 expression has been reported in patients with GV compared with controls and patients with stable vitiligo . Significant reduction in FoxP3 + Tregs and a significant increase in CD4 + and CD8 + T cells was detected in marginal skin in cases of both stable and active vitiligo, suggesting a defect in Tregs in the perilesional skin of both stable and active vitiligo …”
Section: Discussionmentioning
confidence: 90%
“…A decrease in CD4 + /CD8 + ratio and Tregs, and reduced FoxP3 expression has been reported in patients with GV compared with controls and patients with stable vitiligo . Significant reduction in FoxP3 + Tregs and a significant increase in CD4 + and CD8 + T cells was detected in marginal skin in cases of both stable and active vitiligo, suggesting a defect in Tregs in the perilesional skin of both stable and active vitiligo …”
Section: Discussionmentioning
confidence: 90%
“…CD8+ T cells kill self-cells upon antigen recognition and form a critical component of adaptive immunity. These cells have been implicated in the direct killing of melanocytes in vitiligo models[60,73], and thus their recruitment by IL-17 may play an important role in disease pathogenesis[44,7476]. …”
Section: Putative Roles For Il-17 In Vitiligo Pathogenesismentioning
confidence: 99%
“…More recently, repigmentation in a mouse model of spontaneous epidermal depigmentation was found to be accompanied by an increased Treg cell infiltration, suggesting their importance in preventing an ongoing immune response against melanocytes [17]. To date, several studies have indicated perturbations in Treg cell numbers and/or function in vitiligo patients [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 99%
“…Several studies have been carried out to look for alterations in Treg cell numbers in vitiligo (Table 1) [10][11][12][13][14][15][16][17][18][19][20][21][22][23]26,27]. Assessment of circulating Tregs by flow cytometric analysis has revealed a decrease in their numbers in vitiligo patients compared to controls [10,11,13].…”
Section: Regulatory T Cell Numbersmentioning
confidence: 99%
See 1 more Smart Citation